1999
DOI: 10.1038/sj.bjc.6690104
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of care and survival for adolescents and young adults with acute leukaemia – a population-based study

Abstract: SummaryWe report a population-based study of patterns of care and survival for people with acute leukaemia diagnosed at age 15-29 years during 1984-94 in regions of England and Wales covered by specialist leukaemia registries. There were 879 patients: 417 with acute lymphoblastic leukaemia (ALL) and 462 with acute myeloid leukaemia (AML). For ALL, actuarial survival rates were 43% at 5 years after diagnosis and 37% at 10 years. Survival improved significantly between 1984-88 and 1989-94 for those aged 15-19 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 26 publications
2
37
0
3
Order By: Relevance
“…Second, the age-specific OS rates observed in this region were similar to that observed in other regions of the United Kingdom. 4,24 The results clearly demonstrate that the incidence of cytogenetic and immunophenotypic subgroups varies markedly with the age. Although it is known that the incidence of specific chromosomal abnormalities differs between children and adults, the age-specific frequency of such lesions within adult ALL, especially among those older than 60 years of age, was hitherto unknown or poorly studied.…”
Section: Discussionmentioning
confidence: 52%
“…Second, the age-specific OS rates observed in this region were similar to that observed in other regions of the United Kingdom. 4,24 The results clearly demonstrate that the incidence of cytogenetic and immunophenotypic subgroups varies markedly with the age. Although it is known that the incidence of specific chromosomal abnormalities differs between children and adults, the age-specific frequency of such lesions within adult ALL, especially among those older than 60 years of age, was hitherto unknown or poorly studied.…”
Section: Discussionmentioning
confidence: 52%
“…2B). 400-534,600 300-555,000 770-798,200 WBC > 100,000/ll, n (%)* 55 (25) 79 (17) 56 (20) 29 (13) .011 CNS pos., n (%)* 38 (19) 35 (8) 21 (11) n.d. .0002 Extramedullary organ involvement, n (%)* 86 (39) 97 (21) 2 (23) 30 (15) <.0001 FAB** M0, n (%) 13 (6) 24 (5) 14 (5) 13 (6) M1, n (%)…”
Section: Results According To Overlapping and Nonoverlappingmentioning
confidence: 99%
“…For patients of this age group treated in the Medical Research Council (MRC) trials AML9 and AML10, 5-year survival was 55% during the same period. 25 Currently, 5-year survival in children enrolled in clinical trials is in the range of 45% to 60%. 26 In the AML-BFM studies, survival results improved from 49% (period 1987-1992) to 60% (period 1993-1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The lack of clinical trial enrollment in the AYA population is an international problem, as a study from England demonstrated that 80% of patients younger than 14 years with the diagnosis of ALL were enrolled on a clinical trial, while only 36% of patients between the ages of 15 and 29 years did. 53 This lack of clinical trial enrollment has contributed to the difficulty in establishing a "standard of care" for patients in the AYA age-group. In addition, AYA-specific data from clinical trials have historically been extrapolated from data collected within larger trials that include AYAs, but may not have been designed to assess AYA outcomes specifically.…”
mentioning
confidence: 99%